Reproductive Biology, Mating Behavior, and Vibratory Communication of the Brown-Winged Stink Bug, Edessa meditabunda (Fabr.) (Heteroptera: Pentatomidae) - Cleonor Cavalcante A. Silva; Raul Alberto Laumann; Jonatas Barbosa Cavalcante Ferreira; Maria Carolina Blassioli Moraes; Miguel Borges; Andrej Čokl (Psyche: A Journal of Entomology)
We describe different aspects of the reproductive biology, mating behavior, and vibratory communication of the pentatomid Edessa meditabunda (Fabr.). This species shows lower copulation frequency and reproductive potential with longer sexual maturation period compared to other species of pentatomids. Females with multiple mating show increased fecundity when compared with single-mated females and both increased fecundity and reduced longevity when compared with virgin females. Courtship and mating behavior and vibratory signals are typical and similar to what was observed in other species of pentatomids, except that males started the courtship. These results constitute the first paper on biology, behavior, and vibratory communication among species of the subfamily Edessinae.